TINJAUAN ADDENDUM WAKTU PELAKSANAAN PROYEK PEMBANGUNAN JEMBATAN KAMPUNG BARU NAN XX KOTA PADANG - Nasrul, Nasrul; Mulyadi, Beni (Rang Teknik Journal, 2019)
Project management is a scientific discipline in terms of planning, organizing, managing (running and controlling) to be able to achieve project objectives. The role of project management in implementing a construction project is very important, considering the process of implementing construction projects is dynamic. The implementation plan for a project is often preceded by normative assumptions, whereas in the implementation process a lot of unexpected things occur that result in the delay of a job resulting in changes, ranging from weather, environmental social factors to the adjustment of contract volume. One of the compensation for the changes is an extension of the time of contract implementation, but this change certainly must be addressed technically and administratively because without a complete document the changes would certainly not be valid. The contract addendum is one of the valid proofs of a change, because the addendum although physically separate from the principal agreement will be legally addendum still attached to the principal agreement itself. This paper contains the mechanism and conditions for submitting an addendum for the extension of the implementation of the contract so that the addendum is eligible to be accepted in the applicable rules.Keywords: project management, addendum contract, extra time